2014
DOI: 10.1371/journal.pone.0096724
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Education for Whom? — Challenges and Lessons Learned from Its Implementation in Developed Countries and Their Application to Developing Countries: A Systematic Review

Abstract: BackgroundEvidence is available on the potential efficacy of interprofessional education (IPE) to foster interprofessional cooperation, improve professional satisfaction, and improve patient care. While the intention of the World Health Organization (WHO) is to implement IPE in all countries, evidence comes from developed countries about its efficiency, challenges, and barriers to planning and implementing IPE. We therefore conducted this review to examine challenges of implementing IPE to suggest possible pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
203
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(225 citation statements)
references
References 69 publications
(223 reference statements)
5
203
0
17
Order By: Relevance
“…These strategies are corroborated by the findings of a systematic review, which identified that curriculum, leadership, resources, student diversity, teaching and accreditation are important challenges for IPE in developing and developed countries. [13] Implementing a competency framework, based on the competencies of teamwork, responsibilities, communication, learning, patient focus and ethics, could assist the Faculty in setting explicit competencies for the implementation of IPECP. [11] Easing the framework into the curriculum by capitalising on what already exists, effective communication, respect for others and shared decisionmaking, as well as collaborative leadership, problemsolving and conflict resolution, are also important considerations.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies are corroborated by the findings of a systematic review, which identified that curriculum, leadership, resources, student diversity, teaching and accreditation are important challenges for IPE in developing and developed countries. [13] Implementing a competency framework, based on the competencies of teamwork, responsibilities, communication, learning, patient focus and ethics, could assist the Faculty in setting explicit competencies for the implementation of IPECP. [11] Easing the framework into the curriculum by capitalising on what already exists, effective communication, respect for others and shared decisionmaking, as well as collaborative leadership, problemsolving and conflict resolution, are also important considerations.…”
Section: Discussionmentioning
confidence: 99%
“…This program must be housed within a formal program [52] in order to facilitate personalized matching of mentee and mentor [34]. Use of a formal approach facilitates inculcation of training programs for mentors [53,54] and instilling a robust curriculum design that aligns mentoring values and education goals [45,53].…”
Section: Interprofessional Education (Ipe) In Palliative Carementioning
confidence: 99%
“…The presence of mosaic mentors strengthens the benefits of the 4 components of the IPE program. Meetings between mentee and mentors can allow for clarification of didactic content, reinforcement of learning points and most importantly, resolution of conflicts [53] that the mentee may have encountered during clinical rotations. The mentors can enhance the learning value of simulations by providing individualised feedback after the session.…”
Section: Interprofessional Education (Ipe) In Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…While there has been a growth of IPE reviews reporting the effectiveness of this type of education on participants' collaborative competence and ability to deliver safe and effective care (Brandt et al, 2014;Lawlis et al, 2014;Reeves et al, 2013Reeves et al, , 2016Sunguya et al, 2014), little attention has been placed on the facilitation/teaching processes employed by individuals who deliver IPE. In addition, while there has been a growth of qualitative IPE studies, there has been no attempt to synthesise this type of research to assess the nature of the growing qualitative evidence base.…”
Section: Introductionmentioning
confidence: 99%